Analysis of Maxims Used by Receptionists at Hotel Rimbun Canggu: A Pragmatics Study - Daniel Haingu; Ni Nyoman Tri Sukarsih; I Gede Neil Prajamukti Wardhana (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2023)
This study aims to analyze the principles and the degree of maxims found at receptionists. The theory of pragmatics purpose by Yule is linguistic rules in lingual interaction, the rules governing their actions, their use of language, and their interpretations of the actions and utterances of the interlocutor. The method was conducted and the data was taken using descriptive qualitative research using observation and documentation methods. The results that found data to Analysis of Maxims Used by Receptionists at the Hotel Rimbun Canggu: A Pragmatics Study, this research uses 20 data, the first of which is the maxims consisting of the maxim of wisdom with used 3, the maxims of generosity with use 2, the maxims of appreciation with used 3, humility maxims with used 2, consensus/conformity used 3, and the maxim of sympathy uses 3. So, there are 6 maxims used by the receptionist and the data used is 16 data. While the second is the maxims of degree which consists of maxims of quantity, maxim of quality, maxim of relevance, and maxims of manner. The degree of maxims found uses 1 data each, so a total of 4 data is found from the conversations that occur at the receptionists